2019
DOI: 10.14283/jpad.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Standard and Electronic Versions of the Alzheimer’s Disease Assessment Scale – Cognitive Subscale: A Validation Study

Abstract: The Alzheimer’s Disease Assessment Scale (ADAS-Cog) has become the de facto gold-standard for assessing the efficacy of putative anti-dementia treatments. There has been an increasing interest in providing greater standardization, automation, and administration consistency to the scale. Recently, electronic versions of the ADAS-Cog (eADAS-Cog) have been utilized in clinical trials and demonstrated significant reductions in frequency of rater error as compared to paper. In order to establish validity of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…45 In addition, the different findings between the primary and the secondary outcomes also support the notion that the ADAS-cog is the gold standard for the AD clinical trials. 30 In terms of the safety domain, the current study found that all three doses (500, 750, and 1000 mg/day) of benzoate and placebo had similar performance (Table S2). In accordance, the previous studies using flexible-dose sodium benzoate also showed a similar safety profile with that of placebo in early-phase AD (250-750 mg/day), 17 late-life depression (250-1500 mg/day), 20 MCI (250-1500 mg/day), 21 and BPSD (250-1500 mg/day).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…45 In addition, the different findings between the primary and the secondary outcomes also support the notion that the ADAS-cog is the gold standard for the AD clinical trials. 30 In terms of the safety domain, the current study found that all three doses (500, 750, and 1000 mg/day) of benzoate and placebo had similar performance (Table S2). In accordance, the previous studies using flexible-dose sodium benzoate also showed a similar safety profile with that of placebo in early-phase AD (250-750 mg/day), 17 late-life depression (250-1500 mg/day), 20 MCI (250-1500 mg/day), 21 and BPSD (250-1500 mg/day).…”
Section: Discussionmentioning
confidence: 65%
“…It has been well known that early detection and treatment is essential for the outcome of Alzheimer's disease 45 . In addition, the different findings between the primary and the secondary outcomes also support the notion that the ADAS‐cog is the gold standard for the AD clinical trials 30 …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations